Behavior Tokens Speak Louder: Disentangled Explainable Recommendation with Behavior Vocabulary - Feng, Xinshun; Liu, Mingzhe; Qiao, Yi; Zhu, Tongyu; Sun, Leilei; Wang, Shuai (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Recent advances in explainable recommendation have explored the integration of language models to analyze natural language rationales for user–item interactions.Despite their potential, existing methods often rely on ID-based representations that obscure semantic meaning and impose structural constraints on language models, thereby limiting their applicability in open-ended scenarios.These challenges are intensified by the complex nature of real-world interactions, where diverse user intents are entangled and collaborative signals rarely align with linguistic semantics.To overcome these limitations, we propose BEAT, a unified and transferable framework that tokenizes user and item behaviors into discrete, interpretable sequences. We construct a behavior vocabulary via a vector-quantized autoencoding process that disentangles macro-level interests and micro-level intentions from graph-based representations. We then introduce multi-level semantic supervision to bridge the gap between behavioral signals and language space.A semantic alignment regularization mechanism is designed to embed behavior tokens directly into the input space of frozen language models.Experiments on three public datasets show that BEAT improves zero-shot recommendation performance while generating coherent and informative explanations.Further analysis demonstrates that our behavior tokens capture fine-grained semantics and offer a plug-and-play interface for integrating complex behavior patterns into large language models.